SEJARAH MITIGASI BENCANA ERUPSI DI LERENG TIMUR GUNUNG KELUD, 2008-2015 - Rohmah, Utia binti Yuhanni'ur; Ridhoi, Ronald (Handep: Jurnal Sejarah dan Budaya, 2024)
The eruption of Mount Kelud in 2014 showed deviations in eruption characteristics and unpredictability of lava flow direction, and the most severely affected locations were due to volcanic materials. The incident led to the analysis of the eruption and disaster mitigation on the eastern slope of Mount Kelud. In the preparatory process, the authors used a material environmental history approach, integrating Bankoff’s concept of co-volcanic societies and the community’s perception of living harmoniously with hazards in Pandansari Village. This study applied historical research methods, including topic selection, heuristics, source criticism, interpretation, and historiography. The data sources were activity reports, newspapers, photos, maps, and interviews. Findings revealed that the 2014 eruption of Gunung Kelud had a significant impact on Pandansari Village, damaging infrastructures and agricultural land. In addition, this study highlighted the subsequent development of a more systematic disaster mitigation approach implemented by the local community and government in response to the threat of volcanic eruptions.